Specific and non-specific suppressor cell activity in NZB mice. - Cooke, A (1980)
Non-specific and specific suppressor cell activity has been examined in both young and old NZB mice and compared to normal CBA mice. Both young and old NZB mice are shown to be able to generate antigen non-specific and specific suppressor cells in response to Con A and rat RBC respectively. In addition, antigen-specific suppressor cells which suppress the experimental induction of red cell autoantibodies do not influence the spontaneous development or course of autoimmune haemolytic anaemia. Subsequent experiments showed that this is probably due to differences in specificity of induced and spontaneous autoantibodies.